TANTANGAN PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM E-COMMERCE - Rohmah Febriyanti (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
Digital technology disruption has driven economic transformation. E-commerce as a disruptive business model is changing the industrial landscape and people's consumption patterns, bolstered through the deployment of information technology. The integration of Artificial Intelligence (AI) within the realm of information technology simplifies the performance of a range of economic transactions, especially in mapping and processing data related to e-commerce activities. However, the rapid flow of digital technology disruption in the industrial era 5.0 also raises various challenges, especially in legal aspects, such as regarding liability, personal data protection and consumer protection. For this reason, regulatory readiness to regulate and address the dynamics of digital technology disruption in e-commerce is very necessary. Until now, regulations regarding the utilization of information technology, such as AI, have only been generally regulated in Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, Law Number 1 of 2024 jo. Law Number 1 of 2008 concerning Electronic Information and Transactions. Therefore, there is a pressing need to establish the sui generis and clear regulations for the use of information technology in e-commerce. This is essential to address legal concerns related to personal data protection, consumer rights, and the challenges and responsibilities associated with AI in the e-commerce sector.